Diferentes motivos, diferentes comportamentos? A influência da teoria da autodeterminação nos comportamentos de cidadania organizacional e de cidadania organizacional para o meio ambiente - Costa, Vívian Flores (2018)
Given the established relevance of Organizational Citizenship Behaviors (OCB) and Organizational Citizenship Behavior for the Environment (OCB-E) for the functioning and effectiveness of organizations, this study followed the recommendation to explore its additional antecedents when the two are taken together. In this way, he investigated the work motivation as predictor of such denominators, from the perspective of the Self-Determination Theory (SDT). Precisely, the proposal of this study constituted in understanding the influence of Work Motivation, in the light of the Self-Determination Theory, on the Organizational Citizenship Behaviors and the Organizational Citizenship Behaviors for the Environment. For that, a descriptive research was carried out, developed through a bibliographical and field study, using quantitative methodologies for the collection and analysis of the results. Specifically, the study was started with the proposition of an framework for OCB and OCB-E, bringing as background the Work Motivation, in light of the SDT. Following, based on the protocol of Guillemin, Bombardier and Beaton (1993) and Beaton et al. (2000), the translation and cross-cultural adaptation to the Brazilian context of the Organizational Citizenship Behavior for the Environment scale of Boiral and Paillé (2012) was carried out. In order to fulfill the other purposes of this thesis, the data obtained in the application of a questionnaire, based on the Organizational Citizenship Behavior Scale of Bastos, Siqueira and Gomes (2014), Organizational Citizenship Behavior for the Environment scale of Boiral and Paillé (2012), translated and adapted to the national context in this study, and Multidimensional Work Motivation Scale, by Gagné et al. (2015) and Santos et al. (2016), to 926 employees of a private service company, which provides cleaning, maintenance and security services in Rio Grande do Sul. Data were analyzed with the support of IBM SPSS Statistics 22 and IBM SPSS AMOS 18, through the Structural Equations Modeling (SEM). At this moment, the five hypotheses defined from the theoretical arguments presented were confirmed. In general terms, the main results found indicated a relation of influence of Work Motivation, in the light of the Self-Determination Theory, on the Citizenship Behaviors, be these general or directed to the environmental improvements. However, it is important to note that in the proposed integrated model, despite the positive and significant influence on both, OCB and OCB-E, a greater impact of work motivation performed on the former was perceived. Such evidence corroborates the delimitation of the distinctive character of those areas.